Anacroneuria flintorum Froehlich 2002 (Plecoptera: Perlidae): Notes, distribution, and life stages association using molecular tools - Almeida, Lucas Henrique De; Gonçalves, Maísa De Carvalho; Novaes, Marcos Carneiro; Paresqui, Rayner Constantino; Bispo, Pitágoras Da Conceição (Zootaxa, 2018)
Specimens of the perlid stonefly Anacroneuria flintorum from different regions of the Brazilian Atlantic Forest along the Atlantic coast of Brazil were studied. In this paper, the nymph of A. flintorum is described based on reared specimens and molecular associations. Additionally, we provide new locality records and comments about variation of the species.